Cultivating grit among college students: a comparative study between traditional physical education and outdoor education - Li, Lun; Chu, ZuWang; Zong, BoBo; Zeng, ZhengYang; Zeng, YuHao; Zhou, Yun (Frontiers in Psychology, 2025)
ObjectiveThis study aims to address the research gap in comparing the effects of traditional physical education and outdoor education on cultivating grit among college students. Through large-scale empirical analysis, it examines the differential benefits of these two approaches, providing a critical evidence base for developing targeted psychological quality cultivation systems in higher education institutions.MethodsComparative analysis method was used on participants consisting of 1,247 college students (traditional physical education: n = 809; outdoor education: n = 438). The original grit scale (Grit-O) was used to measure the grit quality of university students from seven universities in China before and after 16–18 weeks of both traditional physical education classes and outdoor education classes. The Mann–Whitney U test and the Wilcoxon signed-rank test were used to analyze the overall grit scores, persistence effort, and interest consistency among the participants.ResultsPre-test interest scores of college students in traditional physical education classes were significantly lower than the post-test scores. The differences in total resilience scores, persistence effort, and interest consistency among college students before and after traditional physical education classes and outdoor education classes were statistically significant. There was a significant difference in the total score of grit and persistence effort between male and female college students in traditional physical education course. The total score of grit, persistence effort, and interest consistency before and after outdoor education course were significantly improved. However, male college students showed no significant improvement in their perseverance effort through outdoor education classes.ConclusionThe findings demonstrate that both traditional physical education and outdoor education positively impact on grit of college students, with outdoor education being more effective than traditional physical education in cultivating grit among college students. However, to effectively enhance resilience of college students, traditional physical education need to focus on improving the interest consistency dimension, with a particularly emphasis on increasing persistence and effort dimension within outdoor education for male students.